Perceptions on inclusion of spirituality in counselling among dietitians and nutritionists in Pahang - Razali, Nur Zaliqah Syuhaidah; Mamat, Nik Mazlan (2018)
During the last decades there has been a considerable number of studies showing positive associations between spirituality-religiosity and health. These studies could be unfamiliar to health professionals, because spiritual issues are perceived as personal and private. This present study was conducted to explore the perception and readiness to discuss about spirituality issues during counselling among dietitians and nutritionists.